2013
DOI: 10.1167/iovs.12-10776
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y Receptors Y1and Y2are Present in Neurons and Glial Cells in Rat Retinal Cells in Culture

Abstract: PURPOSE. Neuropeptide Y (NPY) is one of the most abundant peptides in the central nervous system (CNS), including the retina. This peptide activates various different G-coupled receptors (NPY Y 1 , Y 2 , Y 4 , and Y 5 ) that are also present in the retina. However, the localization of NPY receptors in the several types of retinal cells is not completely known. In this study, we have looked at the distribution of NPY Y 1 and Y 2 receptors in rat retinal cells to reveal new perspectives on the role of NPY recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 110 publications
(103 reference statements)
2
28
0
Order By: Relevance
“…In several studies NPY-IR was not detected in the ONL of goldfish, killifish, guinea pig, dolphin and dog (Chen et al, 1999;Kang et al, 2001;Osborne et al, 1985;Subhedar et al, 1996). We have recently shown that rhodopsin-positive cells in rat retinal cell cultures are also immunoreactive for NPY Y 1 and Y 2 receptors (Santos-Carvalho et al, 2013a). Moreover, in adult rat retinal slices we confirmed that NPY Y 1 -and Y 2 -IR localizes in the retina ONL (Santos-Carvalho et al, 2013a).…”
Section: Localization and Functions Of Npy And Npy Receptors In Retinsupporting
confidence: 74%
See 3 more Smart Citations
“…In several studies NPY-IR was not detected in the ONL of goldfish, killifish, guinea pig, dolphin and dog (Chen et al, 1999;Kang et al, 2001;Osborne et al, 1985;Subhedar et al, 1996). We have recently shown that rhodopsin-positive cells in rat retinal cell cultures are also immunoreactive for NPY Y 1 and Y 2 receptors (Santos-Carvalho et al, 2013a). Moreover, in adult rat retinal slices we confirmed that NPY Y 1 -and Y 2 -IR localizes in the retina ONL (Santos-Carvalho et al, 2013a).…”
Section: Localization and Functions Of Npy And Npy Receptors In Retinsupporting
confidence: 74%
“…In relation to the NPY receptors in ganglion cells, we have shown the presence of NPY Y 1 and Y 2 receptors-IR in ganglion cells (Brn3a-positive cells) in rat retinal cell cultures (Santos-Carvalho et al, 2013a). In addtion, both receptors were detected in GCL in rat retinal slices (Santos-Carvalho et al, 2013a).…”
Section: Horizontal Cellsmentioning
confidence: 83%
See 2 more Smart Citations
“…The cells were maintained at 37°C in a humidified atmosphere of 5% CO 2 . These retinal cell cultures are composed of neurons (photoreceptors, bipolar cells, horizontal cells, amacrine cells and RGCs), and glial cells (Müller cells, astrocytes and microglia), as previously described (Santos-Carvalho et al, 2013a).…”
Section: Primary Rat Retinal Neural Mixed Culturementioning
confidence: 99%